1990
DOI: 10.1128/jb.172.12.7282-7283.1990
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequences required for the alkalophily of Bacillus sp. strain C-125 are located close together on its chromosomal DNA

Abstract: Two alkali-sensitive mutants of alkalophilic Bacillus sp. strain C-125 were obtained. Mutant 38154 showed defective regulation of internal pH. Plasmids pALKi and pALK2, containing DNA fragments different from those of the parent strain, were able to recover alkalophily in mutants 18224 and 38154, respectively. DNA analysis suggested that the two fragments overlapped on the chromosomal DNA of strain C-125.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…C-125 as a model alkalophile for molecular biological study for the following reasons: (i) it grows well on minimal medium, (ii) genes from this strain are expressed well in E. coli, and (iii) an efficient system for plasmid transformation of this strain is now available (Kudo et al, 1990). In this paper, we report the cloning and sequencing of the hag gene from the alkalophilic Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…C-125 as a model alkalophile for molecular biological study for the following reasons: (i) it grows well on minimal medium, (ii) genes from this strain are expressed well in E. coli, and (iii) an efficient system for plasmid transformation of this strain is now available (Kudo et al, 1990). In this paper, we report the cloning and sequencing of the hag gene from the alkalophilic Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…There was one report of a lytic bacteriophage (11) and of an endogenous plasmid from one alkaliphilic strain (18). Recently, Kudo et al (14) reported plasmid transformation of a facultative alkaliphile by a protoplast polyethylene glycol method. With our alkaliphilic strain, however, this precise protocol and several variations of it did not prove effective.…”
mentioning
confidence: 99%
“…strain C_125 14 ) was the source of the groEL gene. 15]) was used as the host strain for cloning. Plasmids pUCI18 and 119 were purchased from Takara Shuzo Co., Ltd. (Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%